Cutting NiTi with Femtosecond Laser - L. Quintino; L. Liu; R. M. Miranda; R. J. C. Silva; A. Hu; Y. Zhou (Advances in Materials Science and Engineering)
Superelastic shape memory alloys are difficult to machine by thermal processes due to the facility for Ti oxidation and by mechanical processes due to their superelastic behavior. In this study, femtosecond lasers were tested to analyze the potential for machining NiTi since femtosecond lasers allow nonthermal processing of materials by ablation. The effect of processing parameters on machining depth was studied, and material removal rates were computed. Surfaces produced were analyzed under SEM which shows a resolidified thin layer with minimal heat affected zones. However, for high cutting speeds, that is, for short interaction times, this layer was not observed. A depletion of Ni was seen which may be beneficial in biomedical applications since Ni is known to produce human tissue reactions in biophysical environments.